Geographical Imagination, Anthropology, and Political Exiles: Photographers of Siberia in Late Imperial Russia. Issue 1 (1st March 2020) - Saburova, Tatiana
Abstract: This article is focused on several themes connected with the history of photography, political exile in Imperial Russia, exploration and representations of Siberia in the late 19th–early 20th centuries. Photography became an essential tool in numerous geographic, topographic and ethnographic expeditions to Siberia in the late 19th century; well-known scientists started to master photography or were accompanied by professional photographers in their expeditions, including ones organized by the Russian Imperial Geographic Society, which resulted in the photographic records, reports, publications and exhibitions. Photography was rapidly spreading across Asian Russia and by the end of the 19th century there was a photo studio (or several ones) in almost every Siberian town. Political exiles were often among Siberian photographers, making photography their new profession, business, a way of getting a social status in the local society, and a means of surviving financially as well as intellectually and emotionally. They contributed significantly to the museum's collections by photographing indigenous people in Siberia and even traveling to Mongolia and China, displaying "types" as a part of anthropological research in Asia and presenting "views" of the Russian empire's borderlands. The visual representation of Siberia corresponded with general perceptions of an exotic East, populated by "primitive" peoples devoid of civilization, a trope reinforced by numerous photographs and depictions of Siberia as an untamed natural world, later transformed and modernized by the railroads construction.